If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 15 = 3y + -1 Reorder the terms: 15 + 2y = 3y + -1 Reorder the terms: 15 + 2y = -1 + 3y Solving 15 + 2y = -1 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 15 + 2y + -3y = -1 + 3y + -3y Combine like terms: 2y + -3y = -1y 15 + -1y = -1 + 3y + -3y Combine like terms: 3y + -3y = 0 15 + -1y = -1 + 0 15 + -1y = -1 Add '-15' to each side of the equation. 15 + -15 + -1y = -1 + -15 Combine like terms: 15 + -15 = 0 0 + -1y = -1 + -15 -1y = -1 + -15 Combine like terms: -1 + -15 = -16 -1y = -16 Divide each side by '-1'. y = 16 Simplifying y = 16
| -90=6(7n-1) | | 23X-2=16X+51 | | 1x(3x-10)=90 | | y=0.5x+6.18 | | 5(x-11-7)=16 | | 5x+2+7x=180 | | 5+18=35 | | x=38+x | | 4p-13p+1p=-150 | | 60=3*2y+3*4 | | 2(x-5)-6x=-22 | | X+7=x+(-2) | | -59+x= | | 3z+5=3z+5 | | 9(x+5)=3(x-3)+6x | | 3z+5+6z+4=9z+9 | | x-59= | | 8r+3s=66 | | -8x-9=-3(x+3)-5x | | (x+2y)and(2x-3y)= | | 3X-3.9=-4.1 | | (x+5)(y-6000)=600000 | | 24=6*(x-7) | | logx^2=5 | | 2x^2+34x+17=0 | | 12n+9=6 | | (x+3)(x+4)+(x+6)(x-3)= | | 19=-(5x+7) | | 4(y-7)=5-(6y-2) | | C=39.45+0.25x | | 8z=3 | | 7(4x+2)=42 |